GE_GERICHTE P/20011/2015 vom 8. März 2017 - GE Cour de justice (2017)
RECEL ; SÉJOUR ILLÉGAL ; COMMERCE DE STUPÉFIANTS ; SURSIS À L'EXÉCUTION DE LA PEINE ; RÉVOCATION(EN GÉNÉRAL) | LStup.19.1 LStup.19a.1 CP.160 LEtr.115.1.b LEtr.119.1 CP.42 CP.49 CP.46